Urbanizing at the Lake’s Edge: Watershed Planning and Governance Lessons from the Laguna de Bay Region, Philippines - Gomez, Jr., José Edgardo A. (Journal in Urban and Regional Planning; Vol 1 No 1 (2014): Journal in Urban and Regional Planning)
Planning and implementation at the watershed level is often “easier said than done”, especially in developing countries where there may yet be a lack of shared perspective, reliable data and comprehensive state control over vast basins of territory. In the Philippines, pressures of urbanization and climate change have refocused attention on public administration of freshwater resources and the agencies that regulate water use. This study highlights the Laguna Lake Development Authority and its attempts to delegate management in the Santa Rosa sub-basin of the watershed. It analyzes how differences of mandate at regional and local levels make control of a common resource problematic. The research reviews multiple-agency dynamics that go into planning a common resource vis-à-vis experiences from those who govern and use the lake, then makes practical recommendations for improvement. Keywords: watershed governance, Laguna de Bay, clustering, tragedy of the commons
Keywords: watershed governance, Laguna de Bay, clustering, tragedy of the commons